(untitled) (Archaeologia Adriatica, 2025)
Mollusc shells are among the earliest raw materials used by humans for production of ornaments. They attracted the members of the Homo genus since the Middle Palaeolithic with their colours, shapes, surface texture, as well as their origin (from sea shores, from large distances, etc.). During the Neolithic and Eneolithic period, shells continued to be used for production of diverse objects, especially decorative, and marine shells Spondylus and Glycymeris were particularly widespread in most of Europe. Their distribution shows a vivid trade and exchange network that existed among the prehistoric communities, but also reflects symbolic values. The distribution of the mollusc shell jewellery, their shapes, modes of use, symbolic values, are constantly being enlarged by new findings and new data, thus contributing to a better understanding of the mollusc shell ornament phenomenon. In this paper, decorative objects made from shells will be presented that were discovered during the archaeological research activities at the site of Hermanov Vinograd in Osijek, from contexts attributed to the Sopot culture.